2018
DOI: 10.1186/s12877-018-0898-9
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive anterior muscle-sparing versus a transgluteal approach for hemiarthroplasty in femoral neck fractures-a prospective randomised controlled trial including 190 elderly patients

Abstract: BackgroundThe relevance of femoral neck fractures (FNFs) increases with the ageing of numerous societies, injury-related decline is observed in many patients. Treatment strategies have evolved towards primary joint replacement, but the impact of different approaches remains a matter of debate. The aim of this trial was to evaluate the benefit of an anterior minimally-invasive (AMIS) compared to a lateral Hardinge (LAT) approach for hemiarthroplasty in these oftentimes frail patients.MethodsFour hundred thirty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 63 publications
0
35
0
Order By: Relevance
“…All four studies (5,20,26,32) concluded that no statistically significant difference in the risk of infection was observed between PA and AA, and we did not detect a statistically significant difference when we performed an aggregate analysis (OR: 1.85 95% CI: 0.77-4.43 I 2 = 0% P = 0.17 Figure 7A). We obtained the same conclusion in the PA and LA studies (19, 23, 27, 29, 34-36, 38, 42) (OR: 1.18 95% CI: 0.87-1.59 I 2 = 0% P = 0.28 Figure 7B).…”
Section: Wound Infectionsmentioning
confidence: 76%
See 2 more Smart Citations
“…All four studies (5,20,26,32) concluded that no statistically significant difference in the risk of infection was observed between PA and AA, and we did not detect a statistically significant difference when we performed an aggregate analysis (OR: 1.85 95% CI: 0.77-4.43 I 2 = 0% P = 0.17 Figure 7A). We obtained the same conclusion in the PA and LA studies (19, 23, 27, 29, 34-36, 38, 42) (OR: 1.18 95% CI: 0.87-1.59 I 2 = 0% P = 0.28 Figure 7B).…”
Section: Wound Infectionsmentioning
confidence: 76%
“…Detailed descriptions of the characteristics and patient demographics for each study are listed in Table 1. Five were randomized controlled trials (5,(17)(18)(19)(20) (RCTs) including 588 hips and the others were cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies in this systematic review and meta-analysis mentioned the experience of participating surgeons. Five studies described the number of years of experience of included surgeons 14,18,19,21,23 , 5 studies stated that surgeons were “experienced,” 13,17,26,27,30 , 3 studies described the primary approach used by surgeons in their practice 16,20,28 , 4 studies described the presence of arthroplasty fellowship training 22,24,25,29 , and 1 study stated that all of the surgeons were arthroplasty fellowship trainees in France 15 . Of the 4 studies that described the presence of arthroplasty fellowship training, only 2 described the approach that surgeons were trained to use 25,29 .…”
Section: Resultsmentioning
confidence: 99%
“…No statistically significant differences were found for any of the outcome measures. Saxer et al 34 compared the Smith-Petersen approach with a transgluteal approach, and found no statistically significant difference in the primary outcome, the TUG performance, at three weeks.…”
Section: Discussionmentioning
confidence: 99%